Effects of protein nutrition levels on milk yield, composition, amino acid profiles and plasma metabolites of indigenous lactating buffaloes - Islam, Md. Zakirul; Rahman, S.M. Rajiur; Islam, Md. Nurul; Khandakar, Md. Mehedi Hasan; Siddiki, Mohammad Shohel Rana; Sarker, Nathu Ram; Meenongyai, Watcharawit; Md. Harun-ur-Rashid (Agriculture and Natural Resources, 2022)
The dietary crude protein (CP) supply was optimized for indigenous lactating buffaloes in Bangladesh. Twelve buffaloes (age 4 yr) with an average daily milk yield of 2.33–3.03 kg/d and average ± SD body weight of 390 ± 10 kg were divided into three groups (each with four animals) that were randomly assigned to three levels of CP in the concentrate feed mixture: 14.22%, 15.62%, and 17.81% (dry matter basis) in a completely randomized design. The total duration of the study was 100 d with an initial 10 d of adjustment. The diets were formulated to ensure the same energy level. The dietary protein level showed no effect on dry matter intake (p > 0.05). The nitrogen intake of buffaloes increased linearly (p = 0.01) with increasing CP levels. The milk yield tended to increase in a quadratic fashion. No effect was observed (p > 0.05) on the milk protein, fat and lactose contents. The level of plasma urea nitrogen increased (p < 0.05) when the dietary CP levels were raised, whereas the glucose, protein, albumin, globulin, calcium and triacylglycerol levels remained unchanged (p > 0.05). The nitrogen efficiency of lactating buffaloes increased (p < 0.05) by optimizing dietary protein nutrition accurately to each animal’s requirements. The milk amino acid composition was unaffected (p > 0.05) by the dietary CP supplies. In conclusion, the 15.62% CP level resulted in higher milk production (p < 0.05) and high nitrogen efficiency (p < 0.05) in the indigenous lactating buffaloes under the study conditions.